Strategi Guru dalam Mengoptimalkan Interaksi Sosial untuk Pembentukan Karakter Islami di Sekolah - Yusnita Hikmawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Islamic character development in schools is increasingly relevant to the challenges of globalization that impact students' social interactions. This study aims to identify teacher strategies in optimizing social interactions to develop Islamic character, such as noble morals, tolerance, and monotheism-based leadership. This approach uses a descriptive qualitative approach used with a case study in two Islamic-based secondary schools in Indonesia, involving participant observation, in-depth interviews with 15 teachers, and analysis of curriculum documents. The results of the study on Islamic character show that effective strategies include engaging in Qur'an-based group discussions, Islamic social role simulations, fostering excursions to Muslim communities, and the use of digital technology for collaboration between students. This optimized social interaction has been shown to increase empathy, responsibility, and the values ​​of Islamic brotherhood in students. The implications of the study emphasize the need for teacher training in Islamic interactive pedagogy and a revision of the national curriculum to support holistic character formation.